2015
DOI: 10.1103/physreva.91.022305
|View full text |Cite
|
Sign up to set email alerts
|

Rapid readout of a register of qubits using open-loop quantum control

Abstract: Measurements are a primitive for characterizing quantum systems. Reducing the time taken to perform a measurement may be beneficial in many areas of quantum information processing. We show that permuting the eigenvalues of the state matrix in the logical basis, using open-loop control, provides an O(n) reduction in the measurement time, where n is the number of qubits in the register. This reduction is of the same order as the (previously introduced) locally optimal feedback protocol. The advantage of the open… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Introduction -Quantum monitoring equations play a key role in modern theoretical quantum physics and are used widely in control [1][2][3], quantum information [4][5][6], and even foundations [7,8]. They describe a system subjected to iterated or continuous measurements and can be used to treat a large variety of experimental setups e.g.…”
mentioning
confidence: 99%
“…Introduction -Quantum monitoring equations play a key role in modern theoretical quantum physics and are used widely in control [1][2][3], quantum information [4][5][6], and even foundations [7,8]. They describe a system subjected to iterated or continuous measurements and can be used to treat a large variety of experimental setups e.g.…”
mentioning
confidence: 99%
“…In any case, these numerical simulations show that the asymptotic speed-up should not be the only metric used to assess the efficiency of rapid measurement schemes in the future as the asymptotic regime may be irrelevant in realistic setups. Note that the previous schemes of Combes et al [1,4] which could only be probed numerically for small registers, also showed lower performances for finite infidelity targets. All these reserves being made, the GC algorithm does provide a large speed-up in absolute value for all register sizes and reasonably small infidelity targets.…”
Section: Numericsmentioning
confidence: 86%
“…One expects that, on average, the states will be at a Hamming distance of order n/2 from each other yielding the same kind of speed-up as before but for a different pre-factor. And indeed, in [4] the authors prove that the speed-up S RP for the open-loop random permutation scheme verifies for large n:…”
Section: Standard Rapid Measurement Schemesmentioning
confidence: 87%
See 2 more Smart Citations